Untangling the emergency: fimbrial cyst in pregnancy - B. S., Girija; V., Nayanashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Torsion of uterine adnexa is a significant cause of acute pain abdomen, however isolated fimbrial cyst torsion without the involvement of the ipsilateral ovary is rarely reported. It is even rarer to occur during pregnancy, hence making its diagnosis a conundrum. Here is a case report of a 19 year primigravida with 18 weeks of gestation who presented with acute pain abdomen with investigations suspecting an ovarian torsion. However, on laparotomy, isolated right fimbrial cyst torsion was seen for which detorsion followed by right salpingectomy was done. Adnexal torsion is a surgical emergency requiring early intervention to salvage the tissues. An acute abdomen on the background of adnexal mass requires vigilant assessment and evaluation to ensure timely intervention and prevent further complications.